Das necessidades de formação docente à formação contínua de professores da Educação Infantil - Campos, Rebeca Ramos (2017)
The following study had as its objective the development of an ongoing training course guided by the Teacher Training Needs of Early Childhood/Pre-School Teachers. Subscribed in the Qualitative Approach to Research, it used the Case Study and Action Research Methodologies. In order to construct the data, questionnaire, semi-structured interview, participant observation, field notes, class diaries and document analysis were used. The empirical field was a Municipal Early Childhood Education Center located in the east side of the city of Natal/RN. The research had two data analysis steps, both guided by principles of Content Analysis, in accordance to Bardin (2011) and Franco (2013). Results of the first step verified that, in the care and education of children, the teachers experienced formative needs: in the planning of didactic-pedagogical activities; in the development of the pedagogical practice in the orality, reading, writing, mathematical language and multiple language axis; in support to the teacher training itself; in understanding the thinking of preschool children; in individualized care, on rules and limits, to all children, particularly those with special educational needs; in the family x school relation; in the better use of the inappropriate physical spaces; in improving pedagogical practice, despite the scarcity of materials. In the context of the needs indicated by the investigation, the group elected ‘Reading and Writing’, as the main theme of the ongoing training entitled: Didactic-pedagogical Actions to build orality, reading and writing practices in the Early Childhood/Pre-School Education. As categories of the main theme, emerged the programmatic contents of the training (second step of the research): conceptions of child, childhood and culture; planning in the Early Childhood/Pre-School Education; building/creation of school activities; basic literacy and literacy; psychogenesis of written language; reading and production of texts. The methodological procedures of the training were organized in reflexive reading sessions, participant observation and theory-practice articulation, developed in observations and fortnightly meetings. The evaluation, as an ongoing training process, was carried out from records in class diaries, planning and practices reconstructions and the shared dialogue during the training meetings. The formative action was well evaluated by the teachers, highlighting an evident progress in theoretical-methodological knowledge, in addition to overcoming difficulties in planning, in orality, reading and writing practices with children and in building ‘homework’. The results of the research confirm the thesis that an ongoing training for Early Childhood Education teachers, which takes into consideration their training needs, contributes to overcoming the difficulties found in the development of the pedagogical practice with children.